2009
DOI: 10.3390/ijerph6041485
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Smoking in Young People: A Systematic Review of the Impact of Access Interventions

Abstract: Abstract:Aims: To examine existing evidence on the effectiveness of interventions that are designed to prevent the illegal sale of tobacco to young people. The review considers specific sub-questions related to the factors that might influence effectiveness, any differential effects for different sub-populations of youth, and barriers and facilitators to implementation. Methods: A review of studies on the impact of interventions on young people under the age of 18 was conducted. It included interventions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 20 publications
0
32
1
2
Order By: Relevance
“…While raising the age of sale appears to have had positive effects, and may have contributed to a decline in youth smoking prevalence (Millett, Lee, Gibbons, & Glantz, 2011), young smokers are still able to circumvent this legislation through the apparent support of some local people and retailers, as has been found in other countries (Richardson et al, 2009;Stead & Lancaster, 2005). These findings suggest that retailer education, while essential, will not be sufficient to address this problem, particularly in disadvantaged communities where smoking is still the norm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While raising the age of sale appears to have had positive effects, and may have contributed to a decline in youth smoking prevalence (Millett, Lee, Gibbons, & Glantz, 2011), young smokers are still able to circumvent this legislation through the apparent support of some local people and retailers, as has been found in other countries (Richardson et al, 2009;Stead & Lancaster, 2005). These findings suggest that retailer education, while essential, will not be sufficient to address this problem, particularly in disadvantaged communities where smoking is still the norm.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, significant resources have been invested by the Scottish Government, via local authorities and trading standards officers, in the Enhanced Tobacco Sales Enforcement Initiative (ETSEP). Previous studies in other countries have found that the combination of strategies used in ETSEP, that is, retailer education, sustained enforcement, and graduated penalty schemes, increase retailer compliance with age of sales laws (DiFranza, 2012;Richardson et al, 2009;Stead & Lancaster, 2005). However, in 2009/2010.6% of retailers in Scotland subject to test purchases failed (SCOTTS, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco consumption in adolescents is a major public health problem as most adult smokers start smoking before the age of 18 ( Giovino, 1999 ;Richardson et al, 2009 ) and smokers who start smoking in adolescence have less chances of quitting than those who start later in life ( Khuder, Dayal, & Mutgi, 1999 ). Tobacco companies are also known to consider youth a priority for promotion and sponsorship campaigns ( Braun, Mejia, Ling, & Perez-Stable, 2008 ;Gilpin, White, Messer, & Pierce, 2007 ;Ling & Glantz, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Completely preventing children from observing parental smoking is likely to be an elusive goal, but smoking uptake can be prevented in other ways such as restricting young people's access to cigarettes 14 15. Reviews have shown that legislative restrictions on the purchase of cigarettes by young people are effective when concurrent measures are taken to ensure that retailers obey such laws 14 15.…”
mentioning
confidence: 99%
“…Reviews have shown that legislative restrictions on the purchase of cigarettes by young people are effective when concurrent measures are taken to ensure that retailers obey such laws 14 15. Previous studies have generally investigated the impact of restrictions on the purchase of cigarettes by young persons and not on their smoking behaviour; the few studies that have looked for a link between purchase restrictions and smoking prevalence have found none 14. However, Millett and colleagues use robust national survey data to demonstrate that increasing the legal purchase age of cigarettes in the UK (from 16 to 18 years) caused concurrent reductions in smoking by English children aged 11–15 years 16.…”
mentioning
confidence: 99%